2021
DOI: 10.26740/lenterabio.v10n3.p302-308
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antibakteri Ekstrak Kulit Buah Kakao (Theobroma cacao L.) Terhadap Staphylococcus epidermidis

Abstract: Staphylococcus epidermidis termasuk dalam genus bakteri Staphylococcus yang banyak ditemukan pada infeksi kulit. Pemberian antibiotik pada penyakit kulit yang tidak tepat akan menaikkan tingkat resistensi bakteri. Peningkatan daya resistensi bakteri terhadap antibiotik, memyebakan dilakukan eksplorasi sumber senyawa bioaktif pada bahan alam di Indonesia, salah satunya kakao. Kulit buah kakao adalah bagian yang tidak termanfaatkan dalam pengolahan biji kakao, dan diketahui mengandung senyawa bioaktif dari metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results of the antibacterial inhibition test from the liquid hand washing soap sample obtained the average diameter of the inhibition zone at each concentration; namely a 3% concentration of 8.27 mm, 6% concentration of 10.55 mm, and 9% concentration of 11.16 mm and the soap base control has no inhibition zone. This is in line with research conducted by Utami (2020), which states that the greater the concentration in each formulation, the greater the inhibition of the bacteria (Maramis & Asri, 2022;Mulyani & Hendick, 2022;Mudjahid et al, 2022).…”
Section: Resultssupporting
confidence: 89%
“…The results of the antibacterial inhibition test from the liquid hand washing soap sample obtained the average diameter of the inhibition zone at each concentration; namely a 3% concentration of 8.27 mm, 6% concentration of 10.55 mm, and 9% concentration of 11.16 mm and the soap base control has no inhibition zone. This is in line with research conducted by Utami (2020), which states that the greater the concentration in each formulation, the greater the inhibition of the bacteria (Maramis & Asri, 2022;Mulyani & Hendick, 2022;Mudjahid et al, 2022).…”
Section: Resultssupporting
confidence: 89%
“…The results of this study showed that the tannin content of cocoa fruit skin in Toraja Regency was 12.679% (Pappa et al, 2019). Cocoa pod skin has antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis and is also antiparasitic (Adha & Ibrahim, 2021;Lestari et al, 2021;Pappa et al, 2019). Cocoa shell extract has strong antioxidant activity with an IC50 value of 17.21 ppm (Hidayah et al, 2021;Priani et al, 2021;Ulfa et al, 2019) and has sunscreen activity (Khoiriyah et al, 2022;Priani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%